Early onset ovarian hyperstimulation syndrome despite use of segmentation approach and ovarian hyperstimulation syndrome prophylaxis - Nalini Mahajan; Shalu Gupta; Shilpa Sharma; Kumkum Rani; Padmaja Naidu; Puneet R Arora (Wolters Kluwer Medknow Publications, 2015)
We report a case of early onset severe ovarian hyperstimulation syndrome (OHSS) presenting with oliguria in an antagonist cycle triggered with GnRH agonist and a freeze-all approach. Prophylactic measures in the form of GnRH antagonist, cabergolin and plasma expanders were given after oocyte retrieval. Twenty-four hours after oocyte retrieval patient developed oliguria and moderate ascites. She was managed in ICU with albumin and diuretics. She responded to conservative management and did not require paracentesis. Severe OHSS can occur in PCOS patients even after using a segmented approach i.e. GnRH agonist trigger with a 'freeze all' policy. Patients at risk of OHSS should be closely monitored following ovum pickup even when an agonist trigger has been given, for early detection and management.